Photooxidation Mechanism of Levomepromazine in Different Solvents. (10th September 2013) - Piñero‐Santiago, Luis E.; García, Carmelo; Lhiaubet‐Vallet, Virginie; Trzcionka, Jerome; Oyola, Rolando; Torres, Karen; Leguillú, Jaysika; Miranda, Miguel A.
Abstract: Unwanted photoinduced responses are well‐known adverse effects of most promazine drugs, including levomepromazine (LPZ, Levoprome ® or Nozinan ® ). This drug is indicated in psychiatry primarily for the treatment of schizophrenia and other schizoaffective disorders. Levomepromazine's particular sedative properties make it especially fit for use in psychiatric intensive care. Nevertheless, it is photolabile under UV‐A and UV‐B light in aerobic conditions resulting in the formation of its sulfoxide. The LPZ photochemistry in acetonitrile (MeCN) is completely different from that in methanol (MeOH) and phosphate buffer solutions (PBS, pH = 7.4). The major photoproduct in PBS and MeOH under aerobic conditions is levomepromazine sulfoxide (LPZSO), although the amount is considerably higher in the aqueous environment. The corresponding main photoproduct in MeCN could not be characterized. The destruction quantum yields of LPZ in PBS, MeOH and MeCN are 0.13, 0.02 and <10 −3, respectively. It is further demonstrated that LPZSO does not form by the reaction of singlet oxygen with ground‐state LPZ. This oxidation product is actually produced by the reaction of the cation radical of LPZ (LPZ· + ) with molecular oxygen. This cation radical in turn, is produced by an electron transfer process between the 3 LPZ* and ground‐state molecular oxygen. Abstract : Levomepromazine (LPZ, Levoprome ® or Nozinan ® ) is indicated for the treatment of schizophrenia and other schizoaffective disorders. Nevertheless, it is photolabile under UV‐A and UV‐B light in aerobic conditions resulting in the formation of its sulfoxide (LPZO). LPZSO does not form by the reaction of singlet oxygen with ground state LPZ. This oxidation product is actually produced by the reaction of the cation radical of LPZ (LPZ· + ) with molecular oxygen. This cation radical in turn, is produced by an electron transfer process between the 3 LPZ* and ground state molecular oxygen.